Talking about maps : IV (Historia, 2021)
In the last chapter we left an increasing number of Christians engaged upon pilgrimages to the Holy Land, which preceded the crusades, called forth by further invasion from Asia. Just as earlier Asiatic clans had made their way into Europe, so now did the Seljuk Turks. In t~e 8th century Slavs had entered along the Danube, and in the 9th another horde, the Bulgars. The Seljuks expelled an earlier immigrant leader ruling in eastern Persia. Bagdad fell, but the newcomers embraced Mohammedanism and kept in office both Arab and Persian. The Byzantine empire lost territory in Asia Minor, and in 1071 the Emperor suffered defeat and capture. However, the Turkish Emperor, now entitled "sultan", was merciful (or discreet), and accepted a ransom and the payment of tribute.
Keywords: Portolans; Cartography; Maps; Sea-charts; Travellers